2020
DOI: 10.1074/jbc.ra120.012803
|View full text |Cite
|
Sign up to set email alerts
|

The heme-regulatory motifs of heme oxygenase-2 contribute to the transfer of heme to the catalytic site for degradation

Abstract: Heme-regulatory motifs (HRMs) are present in many proteins that are involved in diverse biological functions. The C-terminal tail region of human heme oxygenase-2 (HO2) contains two HRMs whose cysteine residues form a disulfide bond; when reduced, these cysteines are available to bind Fe3+-heme. Heme binding to the HRMs occurs independently of the HO2 catalytic active site in the core of the protein, where heme binds with high affinity and is degraded to biliverdin. Here, we describe the reversible, protein-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
(78 reference statements)
3
17
0
Order By: Relevance
“…To explore the role of heme binding to the catalytic site in regulating HO2 stability, we generated a catalytic site loss-of-function mutant, H45W/G159W, for expression in HEK293 cells. In vitro experiments have confirmed that in H45W/G159W variant, there is no detectible heme binding at the catalytic site and that the overall structure and heme binding to the HRMs are unperturbed (32). As expected, no changes were observed in steady-state expression levels of the H45W/G159W mutant upon cellular heme level variation (Fig.…”
Section: Resultssupporting
confidence: 70%
“…To explore the role of heme binding to the catalytic site in regulating HO2 stability, we generated a catalytic site loss-of-function mutant, H45W/G159W, for expression in HEK293 cells. In vitro experiments have confirmed that in H45W/G159W variant, there is no detectible heme binding at the catalytic site and that the overall structure and heme binding to the HRMs are unperturbed (32). As expected, no changes were observed in steady-state expression levels of the H45W/G159W mutant upon cellular heme level variation (Fig.…”
Section: Resultssupporting
confidence: 70%
“…To explore the role of heme binding to the catalytic site in regulating HO2 stability, we generated a catalytic site loss-of-function mutant, H45W/G159W, for expression in HEK293 cells. In vitro experiments have confirmed that in H45W/G159W variant, there is no detectible heme binding at the catalytic site and that the overall structure and heme binding to the HRMs are unperturbed (30). As expected, no changes were observed in steady-state expression levels of the H45W/G159W mutant upon cellular heme level variation ( Fig.…”
Section: Resultssupporting
confidence: 70%
“…The marked effect of heme occupancy at the catalytic site on HO2 stability also led us to explore whether increasing heme affinity of the catalytic site would further stabilize HO2 protein, leading to a higher steady-state HO2 level than wild-type. Therefore, the G163H variant, also catalytically inactive (Table S1), however with a 100-fold higher heme affinity of the catalytic site (30), was tested. Surprisingly, both the G163D and G163H variants showed similar steady-state protein levels as wild type, and the G163H variant has a similar half-life as wild-type HO2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations